2011
DOI: 10.1073/pnas.1115888108
|View full text |Cite
|
Sign up to set email alerts
|

Garrod's fourth inborn error of metabolism solved by the identification of mutations causing pentosuria

Abstract: Pentosuria is one of four conditions hypothesized by Archibald Garrod in 1908 to be inborn errors of metabolism. Mutations responsible for the other three conditions (albinism, alkaptonuria, and cystinuria) have been identified, but the mutations responsible for pentosuria remained unknown. Pentosuria, which affects almost exclusively individuals of Ashkenazi Jewish ancestry, is characterized by high levels of the pentose sugar l -xylulose in blood and urine and deficiency of the enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Although the enzyme deficiency responsible for essential pentosuria was identified in 1970 (Wang & Van Eys, 1970), the molecular background was resolved only very recently (Pierce et al, 2011). As a recessive trait, pentosuria has almost exclusively been diagnosed among ethnic groups with a history of endogamy, such as the Ashkenazi Jewish population (Lane & Jenkins, 1985), within which the frequency of pentosuria is one in 3300 individuals (Pierce et al, 2011).…”
Section: Dcxr and Disease -The Multifunctional Nature Of Dcxr (1mentioning
confidence: 99%
“…Although the enzyme deficiency responsible for essential pentosuria was identified in 1970 (Wang & Van Eys, 1970), the molecular background was resolved only very recently (Pierce et al, 2011). As a recessive trait, pentosuria has almost exclusively been diagnosed among ethnic groups with a history of endogamy, such as the Ashkenazi Jewish population (Lane & Jenkins, 1985), within which the frequency of pentosuria is one in 3300 individuals (Pierce et al, 2011).…”
Section: Dcxr and Disease -The Multifunctional Nature Of Dcxr (1mentioning
confidence: 99%
“…The molecular background of this condition, pentosuria, was recently elucidated. 18 To date, two fungal LXRs have been functionally verified to be involved in l -arabinose catabolism, including the NADH-dependent ALX1 of the yeast Am. monospora (19) and the recently identified NADPH-dependent LxrA of A. niger .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, LXR deficiency causes pentosuria, a clinically benign condition that results in large amounts of l -xylulose in the urine of such patients. 18 The first fungal l -xylulose reductase, ALX1, was identified in the yeast Ambrosiozyma monospora and, interestingly, is NADH-dependent. 19 Although an enzyme with l -xylulose reductase (LXR1) was described for T. reesei , 20 its functional characterization showed that it is actually a d -mannitol 2-dehydrogenase.…”
mentioning
confidence: 99%
“…The gene frequency in a North America sample is 1.7 percent, meaning that one in 3300 would be homozygotes. There is no known selective benefit from this condition; its only adverse effect was when bearers were mistakenly diagnosed as diabetic, sometimes resulting in hypoglycemia from ill-advised insulin therapy [103]. …”
Section: From Evolutionary Medicine To Evolutionary Molecular Medicinementioning
confidence: 99%